Exploring the factors that contribute to the successful implementation of antimicrobial resistance interventions: a comparison of high-income and low-middle-income countries - Graells, Tiscar; Lambraki, Irene A.; Cousins, Melanie; Léger, Anaïs; Henriksson, Patrik J. G.; Troell, Max; Carson, Carolee A.; Parmley, Elizabeth Jane; Majowicz, Shannon E.; Wernli, Didier; Jørgensen, Peter Søgaard (Frontiers in Public Health, 2023)
Introduction: Antimicrobial resistance (AMR) is a challenge to modern medicine. Interventions have been applied worldwide to tackle AMR, but these actions are often not reported to peers nor published, leading to important knowledge gaps about what actions are being taken. Understanding factors that influence implementation of AMR interventions and what factors are relevant in low-middle income countries (LMICs) and high-income countries (HICs) were the key objectives of this exploratory study with the aim to identify which priorities these contexts need. Methods: A questionnaire was used to explore context, characteristics and success factors or obstacles to intervention success based on participant input. Context was analysed using the AMRIntervene framework and success factors and obstacles to intervention success were identified using thematic analysis. Results: Of 77 interventions, 57 were implemented in HICs and 17 in LMICs. Interventions took place in the animal sector followed by the human sector. Public organizations were mainly responsible for implementation and funding. Nine themes and 32 sub-themes emerged as important for intervention success. Themes most reported were 'behaviour', 'capacity and resources', 'planning' and 'information'. Five sub-themes were key in all contexts ('collaboration and coordination', 'implementation', 'assessment', 'governance' and 'awareness'), two were key in LMICs ('funding and finances' and 'surveillance, antimicrobial susceptibility testing and preventive screening'), and five were key in HICs ('mandatory', 'multiple profiles', 'personnel', 'management' and 'design'). Conclusions: LMICs sub-themes showed that funding and surveillance were still key issues for interventions while important HICs sub-themes were more specific and detailed including mandatory enforcement, multiple profiles and personnel needed or good management and good design. While behaviour is often underrated when implementing AMR interventions, capacity and resources are usually considered and LMICs can benefit from sub-themes captured in HICs if tailored to their contexts. The factors identified can improve design, planning, implementation and evaluation of interventions.